Nano-enabled bioanalytical approaches to ultrasensitive detection of low abundance single nucleotide polymorphisms. Issue 12 (21st June 2015) - Lapitan Jr., Lorico D. S.; Guo, Yuan; Zhou, Dejian
<x xml:space="preserve">Abstract</x> A survey of the recent, significant developments on nanomaterials enabled ultrasensitive DNA and gene mutation assays is presented.